Groundwater vulnerability assessment in Portugal - Manuel M. Oliveira; J. P. Lobo Ferreira (Geofísica Internacional, 2004)
During the 70’s and 80’s groundwater vulnerability mapping in Portugal was based mainly on the interpretation of geological information in terms of vulnerability to groundwater pollution. In 1987 a parametric method for the assessment vulnerability to pollution was introduced by the USEPA (the DRASTIC index). In 1993 Portugal was the first European Union’s Member-State to have its territory mapped using the DRASTIC index (1:500,000 scale). Since then several applications of the DRASTIC index, at different scales, and using different sources of base information, have been made. The use of different sources of information, with different scales and sometimes with different approaches lead to different final maps of the same area, as shown in this paper for Setúbal peninsula, south of Lisbon. New methodologies for groundwater vulnerability assessment, based on the characterization of different parameters, led to a comparison of the results. With this aim, a comparison between six vulnerability index methods (AVI, GOD, DRASTIC, SI, EPPNA and SINTACS) was carried out for an aquifer system located near Évora (Alentejo, Portugal). Conclusions for further research on vulnerability mapping are addressed at the end of this paper.